Pneumatic tires

By adjusting the structural parameters of the tire and the ratio of the rubber composition, the problem of biased wear of passenger car tires when driving at high speed is solved, and higher wear resistance and comprehensive performance are improved.

CN116141876BActive Publication Date: 2025-03-28SUMITOMO RUBBER INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310345952.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-16
Filing Date
2020-10-14
Publication Date
2025-03-28
Estimated Expiration
2040-10-14

AI Technical Summary

Technical Problem

Existing passenger car tires are prone to wear off when driving at high speeds, resulting in insufficient wear resistance.

Method used

By adjusting the total width of the tire and the buffer layer width, the elongation of the tread rubber composition break and compounding meet certain conditions, improving the wear resistance of the tire.

Benefits of technology

When driving at high speed, the tires are significantly improved withstand wear resistance, and at the same time improve fuel efficiency, wet grip performance and handling stability to achieve a good balance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116141876B_ABST
    Figure CN116141876B_ABST
Patent Text Reader

Abstract

Pneumatic tire with an aspect ratio of 35% to 70%, Y is defined by the following formula: Y = (B-16) / A, wherein A is the total width of the tire (mm), B is the width of the tire buffer layer (mm), and the range of Y value varies according to the aspect ratio as follows: when the aspect ratio is greater than 35% and less than 40%, Y is less than 0.80; when the aspect ratio is greater than 40% and less than 45%, Y is less than 0.79; when the aspect ratio is greater than 40% and less than 45%, Y is less than 0.80 .... When the flatness is 45% or more and less than 50%, Y is less than 0.78; when the flatness is 50% or more and less than 55%, Y is less than 0.77; when the flatness is 55% or more and less than 60%, Y is less than 0.75; when the flatness is 60% or more and less than 65%, Y is less than 0.72; when the flatness is 65% or more and less than 70%, Y is less than 0.69; when the flatness is 70%, Y is less than 0.67; wherein, the elongation at break of the tread rubber composition measured under the conditions of 14.0m / tensile rate and 100°C atmosphere is 180% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the following Chinese patent application:

[0002] Original application date: October 14, 2020

[0003] Original application number: 202080026782.X (PCT / JP2020 / 038806)

[0004] Original application name: Pneumatic tire Technical Field

[0005] The present disclosure relates to a pneumatic tire having improved uneven abrasion resistance when running at high speed. Background Art

[0006] There is an increasing demand for achieving a high level of performance (fuel efficiency, wet grip performance, handling stability during high-speed running, etc.) in tires for passenger cars.

[0007] In Patent Document 1, it is considered to use a silane coupling agent having a highly reactive mercapto group (mercapto-based silane coupling agent) together with silica in order to improve fuel efficiency, etc. However, although the mercapto-based silane coupling agent can achieve good fuel efficiency, wet grip performance and wear resistance, the processability tends to deteriorate, and there is still room for improvement in the dispersibility of silica.

[0008] Furthermore, tires for passenger vehicles that are targeted for fuel efficiency have a problem in that uneven wear is likely to occur due to an increase in the tread surface temperature at the shoulder head.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: JP 2009-120819 A Summary of the invention

[0012] Problems to be solved by the present disclosure

[0013] An object of the present disclosure is to provide a pneumatic tire having improved uneven wear resistance during high-speed running.

[0014] Solutions to the problem

[0015] Through in-depth research, the present inventors have found that for tires (preferably passenger car tires) whose total width and buffer layer width of the tire meet predetermined requirements, the eccentric wear resistance during high-speed driving can be improved by making the elongation at break and / or compounding of the tread rubber composition meet specific conditions. In addition, in a preferred embodiment, the present inventors have found that fuel efficiency, wet grip performance, and handling stability during high-speed driving are all improved and have a good balance, thereby completing the present disclosure.

[0016] In other words, the present disclosure relates to:

[0017] [1] A pneumatic tire having a flattening ratio of 35% to 70%, wherein Y is defined by the following formula:

[0018] Y=(B-16) / A

[0019] Wherein, when the tread of a tire (the tire is mounted on a normal rim and is in a normal state with normal internal pressure and no load) is pressed against a flat surface under a normal load, A is the total width of the tire (mm), B is the width of the tire's buffer layer (mm), and the range of the Y value varies according to the aspect ratio as follows:

[0020] When the flatness is 35% or more and less than 40%, Y is 0.80 or less; when the flatness is 40% or more and less than 45%, Y is 0.79 or less; when the flatness is 45% or more and less than 50%, Y is 0.78 or less; when the flatness is 50% or more and less than 55%, Y is 0.77 or less; when the flatness is 55% or more and less than 60%, Y is 0.75 or less; when the flatness is 60% or more and less than 65%, Y is 0.72 or less; when the flatness is 65% or more and less than 70%, Y is 0.69 or less; when the flatness is 70%, Y is 0.67 or less; wherein the elongation at break of the tread rubber composition measured under the following test conditions is 180% or more:

[0021] (Test conditions)

[0022] Tensile rate: 14.0m / s

[0023] Temperature: 100℃

[0024] Specimen: No. 7 dumbbell-shaped specimen.

[0025] [2] The pneumatic tire of [1] above, wherein the tread rubber composition contains styrene-butadiene rubber.

[0026] [3] The pneumatic tire of [1] or [2] above, wherein the tread rubber composition contains silica and a silane coupling agent having a mercapto group.

[0027] [4] A pneumatic tire having an aspect ratio of 35% to 70%, wherein Y is defined by the following formula:

[0028] Y=(B-16) / A

[0029] Wherein, when the tread of a tire (the tire is mounted on a normal rim and is in a normal state with normal internal pressure and no load) is pressed against a flat surface under a normal load, A is the total width of the tire (mm), B is the width of the tire's buffer layer (mm), and the range of the Y value varies according to the aspect ratio as follows:

[0030] When the flatness is 35% or more and less than 40%, Y is 0.80 or less; when the flatness is 40% or more and less than 45%, Y is 0.79 or less; when the flatness is 45% or more and less than 50%, Y is 0.78 or less; when the flatness is 50% or more and less than 55%, Y is 0.77 or less; when the flatness is 55% or more and less than 60%, Y is 0.75 or less; when the flatness is 60% or more and less than 65%, Y is 0.72 or less; when the flatness is 65% or more and less than 70%, Y is 0.69 or less; when the flatness is 70%, Y is 0.67 or less;

[0031] The tread rubber composition comprises a rubber component, silica and a silane coupling agent having a mercapto group, wherein the rubber component comprises styrene-butadiene rubber; the total content of styrene in the styrene-butadiene rubber and the butadiene rubber is 25% by mass or more; and when the content of silica is C (parts by mass) and the average primary particle size of silica is D (nm) relative to 100 parts by mass of the rubber component, C / D is 3.8 or more.

[0032] [5] The pneumatic tire of [4] above, wherein the tread rubber composition has an elongation at break of 180% or more measured under the following test conditions,

[0033] (Test conditions)

[0034] Tensile rate: 14.0m / s

[0035] Temperature: 100℃

[0036] Specimen: No. 7 dumbbell-shaped specimen.

[0037] [6] The pneumatic tire of any one of [2] to [5] above, wherein the styrene butadiene rubber includes modified styrene butadiene rubber.

[0038] [7] The pneumatic tire of any one of [1] to [6] above, wherein the tread rubber composition contains zinc dithiophosphate.

[0039] [8] The pneumatic tire according to any one of [1] to [7] above, wherein the tread rubber composition contains a thiuram-based vulcanization accelerator.

[0040] Effects of the present disclosure

[0041] The pneumatic tire of the present invention (the total width of the tire and the buffer layer width of the tire meet the predetermined requirements and the elongation at break and / or compounding of the tread rubber composition meet specific conditions) is excellent in uneven wear resistance when running at high speed. In addition, in a preferred embodiment, fuel efficiency, wet grip performance and handling stability when running at high speed are improved and have a good balance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 is a schematic diagram of a cut-away section of a tire when the tread is pressed against a flat surface. DETAILED DESCRIPTION

[0043] A first embodiment of the present disclosure is a pneumatic tire having an aspect ratio of 35% to 70%, wherein Y is defined by the following formula:

[0044] Y=(B-16) / A

[0045] Wherein, when the tread of a tire (the tire is mounted on a normal rim and is in a normal state with normal internal pressure and no load) is pressed against a flat surface under a normal load, A is the total width of the tire (mm), B is the width of the tire's buffer layer (mm), and the range of the Y value varies according to the aspect ratio as follows:

[0046] When the flatness is 35% or more and less than 40%, Y is 0.80 or less (preferably 0.79 or less, more preferably 0.78 or less); when the flatness is 40% or more and less than 45%, Y is 0.79 or less (preferably 0.78 or less, more preferably 0.77 or less); when the flatness is 45% or more and less than 50%, Y is 0.78 or less (preferably 0.77 or less, more preferably 0.76 or less); when the flatness is 50% or more and less than 55%, Y is 0.77 or less (preferably 0.76 or less, more preferably 0.75 or less); when the flatness is 55% or more and less than 60 When the flatness is 60% or more and less than 65%, Y is 0.72 or less (preferably 0.71 or less, more preferably 0.70 or less); when the flatness is 65% or more and less than 70%, Y is 0.69 or less (preferably 0.68 or less, more preferably 0.67 or less); when the flatness is 70%, Y is 0.67 or less (preferably 0.66 or less, more preferably 0.65 or less), wherein the elongation at break of the tread rubber composition measured under the following test conditions is 180% or more:

[0047] (Test conditions)

[0048] Tensile rate: 14.0m / s

[0049] Temperature: 100℃

[0050] Specimen: No. 7 dumbbell-shaped specimen

[0051] The JIS standard stipulates that when measuring the elongation at break (elongation at cut), the tensile rate is 500±50mm / min for dumbbell specimens No. 1, No. 2, No. 3, No. 5 and No. 6; and the tensile rate is 200±20mm / min for dumbbell specimens No. 7 and No. 8. Through in-depth research on this tensile rate, it was found that the elongation at break measured at an extremely high tensile rate of 14.0m / s in an atmosphere of 100°C (hereinafter also referred to as rapid high-temperature EB) is closely related to the eccentric wear resistance during high-speed driving. As long as the rapid high-temperature EB is within a specific range, good eccentric wear resistance can be ensured.

[0052] A second embodiment of the present disclosure is a pneumatic tire having an aspect ratio of 35% to 70%, wherein Y is defined by the following formula:

[0053] Y=(B-16) / A

[0054] Wherein, when the tread of a tire (the tire is mounted on a normal rim and is in a normal state with normal internal pressure and no load) is pressed against a flat surface under a normal load, A is the total width of the tire (mm), B is the width of the tire's buffer layer (mm), and the range of the Y value varies according to the aspect ratio as follows:

[0055] When the flatness is 35% or more and less than 40%, Y is 0.80 or less (preferably 0.79 or less, more preferably 0.78 or less); when the flatness is 40% or more and less than 45%, Y is 0.79 or less (preferably 0.78 or less, more preferably 0.77 or less); when the flatness is 45% or more and less than 50%, Y is 0.78 or less (preferably 0.77 or less, more preferably 0.76 or less); when the flatness is 50% or more and less than 55%, Y is 0.77 or less (preferably 0.76 or less, more preferably 0.75 or less). When the flatness is 55% or more and less than 60%, Y is 0.75 or less (preferably 0.74 or less, more preferably 0.73 or less); when the flatness is 60% or more and less than 65%, Y is 0.72 or less (preferably 0.71 or less, more preferably 0.70 or less); when the flatness is 65% or more and less than 70%, Y is 0.69 or less (preferably 0.68 or less, more preferably 0.67 or less); when the flatness is 70%, Y is 0.67 or less (preferably 0.66 or less, more preferably 0.65 or less);

[0056] The tread rubber composition comprises a rubber component, silica and a silane coupling agent having a mercapto group, wherein the rubber component comprises styrene-butadiene rubber; the total content of styrene in the styrene-butadiene rubber and the butadiene rubber is 25% by mass or more; and when the content of silica is C (parts by mass) and the average primary particle size of silica is D (nm) relative to 100 parts by mass of the rubber component, C / D is 3.8 or more.

[0057] In the production of tread rubber composition (tread rubber composition), by combining the rubber component containing styrene-butadiene rubber and silica and silane coupling agent that meet predetermined requirements, it is possible to overcome the deterioration of processability during kneading, ensure the dispersibility of silica in the rubber component, and improve rapid high-temperature EB. In addition, by adopting such compounding, it is also possible to improve the balance of fuel efficiency, wet grip performance, and uneven wear resistance.

[0058] A third embodiment of the present disclosure is a pneumatic tire having an aspect ratio of 35% to 70%, wherein Y is defined by the following formula:

[0059] Y=(B-16) / A

[0060] Wherein, when the tread of a tire (the tire is mounted on a normal rim and is in a normal state with normal internal pressure and no load) is pressed against a flat surface under a normal load, A is the total width of the tire (mm), B is the width of the tire's buffer layer (mm), and the range of the Y value varies according to the aspect ratio as follows:

[0061] When the flatness is 35% or more and less than 40%, Y is 0.80 or less (preferably 0.79 or less, more preferably 0.78 or less); when the flatness is 40% or more and less than 45%, Y is 0.79 or less (preferably 0.78 or less, more preferably 0.77 or less); when the flatness is 45% or more and less than 50%, Y is 0.78 or less (preferably 0.77 or less, more preferably 0.76 or less); when the flatness is 50% or more and less than 55%, Y is 0.77 or less (preferably 0.76 or less, more preferably 0.75 or less). ); when the flatness is 55% or more and less than 60%, Y is 0.75 or less (preferably 0.74 or less, more preferably 0.73 or less); when the flatness is 60% or more and less than 65%, Y is 0.72 or less (preferably 0.71 or less, more preferably 0.70 or less); when the flatness is 65% or more and less than 70%, Y is 0.69 or less (preferably 0.68 or less, more preferably 0.67 or less); when the flatness is 70%, Y is 0.67 or less (preferably 0.66 or less, more preferably 0.65 or less);

[0062] The tread rubber composition comprises a rubber component, silica and a silane coupling agent having a mercapto group, wherein the rubber component comprises styrene-butadiene rubber; the total content of styrene in the styrene-butadiene rubber and the butadiene rubber is 25% by mass or more; when the content of silica is C (parts by mass) and the average primary particle size of silica is D (nm) relative to 100 parts by mass of the rubber component, C / D is 3.8 or more; or, the elongation at break of the tread rubber composition measured under the following test conditions is 180% or more:

[0063] (Test conditions)

[0064] Tensile rate: 14.0m / s

[0065] Temperature: 100℃

[0066] Specimen: No. 7 dumbbell-shaped specimen.

[0067] The manufacturing process of a pneumatic tire (including the production of a rubber composition for a tread according to an embodiment of the present disclosure) will be described in detail below. However, the following description is used to illustratively explain the present disclosure and is not intended to limit the technical scope of the present disclosure to only the description scope. In addition, in this specification, the numerical range represented by "to" represents a numerical value including both ends.

[0068] <Rubber component>

[0069] In the present disclosure, styrene butadiene rubber (SBR) and butadiene rubber (BR) are suitable for use as rubber components for producing rubber compositions for treads. As rubber components, it is preferred to include at least one selected from SBR and BR, more preferably SBR. The rubber component may be a rubber component including SBR and BR, or may be a rubber component consisting only of SBR and BR.

[0070] (SBR)

[0071] There is no particular restriction on SBR, and examples include: solution polymerization SBR (S-SBR), emulsion polymerization SBR (E-SBR), their modified SBR (modified S-SBR, modified E-SBR) etc. The example of modified SBR includes SBR modified at the end and / or main chain, and the modified SBR (condensate or modified SBR with branched structure etc.) coupled with tin, silicon compound etc. Among these, preferably S-SBR and modified SBR, more preferably modified S-SBR. In addition, the hydride (hydrogenated SBR) etc. of these SBRs can also be used. These SBRs can be used alone or in combination of two or more.

[0072] Examples of S-SBR that can be used in the present disclosure include S-SBR manufactured and sold by JSR Corporation, Sumitomo Chemical Co., Ltd., Ube Industries, Ltd., Asahi Kasei Corporation, and ZS Elastomers Co., Ltd.

[0073] In consideration of the grip performance, the styrene content of SBR is preferably 10% by mass or more, more preferably 15% by mass or more, and further preferably 20% by mass or more. On the other hand, the styrene content of SBR is preferably 55% by mass or less, more preferably 50% by mass or less, and further preferably 45% by mass or less. When the styrene content of SBR exceeds 55% by mass, the styrene groups are adjacent to each other, the polymer becomes too hard, and the crosslinking tends to become uneven, which may impair the impact performance during high-temperature driving; the temperature dependence increases, and the performance changes in response to temperature changes become larger, which leads to a tendency that stable grip performance cannot be obtained satisfactorily during driving and in the later period. In addition, in this specification, the styrene content of SBR is expressed by 1 H-NMR measurements calculated.

[0074] In order to ensure the reactivity with silica, rubber strength and wear resistance, the vinyl bond amount of SBR is preferably 10 mol% or more, more preferably 15 mol% or more, and further preferably 20 mol% or more. In addition, in order to prevent the increase of temperature dependence, wet grip performance, elongation at break, and wear resistance, the vinyl bond amount of SBR is preferably 70 mol% or less, more preferably 65 mol% or less, and further preferably 60 mol% or less. In addition, in this specification, the vinyl bond amount of SBR (the amount of 1,2-bonded butadiene units) is measured by infrared absorption spectroscopy.

[0075] In view of wet grip performance and abrasion resistance, the weight average molecular weight (Mw) of SBR is preferably 200,000 or more, more preferably 300,000 or more, further preferably 400,000 or more, and particularly preferably 500,000 or more. In addition, in view of crosslinking uniformity, etc., Mw is preferably 2,000,000 or less, more preferably 1,500,000 or less, and further preferably 1,000,000 or less. In addition, Mw can be calculated based on the measured value obtained by gel permeation chromatography (GPC) (for example, GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, chromatographic column: TSKGEL SUPERMULTIPORE HZ-M manufactured by Tosoh Corporation) with standard polystyrene.

[0076] In consideration of wet grip performance, the content of SBR in the rubber component is preferably 60% by mass or more, more preferably 65% ​​by mass or more, further preferably 70% by mass or more, and particularly preferably 75% by mass or more. In consideration of wear resistance, the content is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less.

[0077] (BR)

[0078] There is no particular limitation on BR, and those commonly used in the tire industry may be used, for example, BR having a cis 1,4 bond content of less than 50% (low cis BR), BR having a cis 1,4 bond content of 90% or more (high cis BR), rare earth butadiene rubber synthesized using a rare earth element catalyst (rare earth BR), BR containing syndiotactic polybutadiene crystals (SPB-containing BR), and modified BR (high cis modified BR, low cis modified BR).

[0079] Examples of high cis BR include, for example, BR1220 manufactured by Zeon Co., Ltd., BR130B, BR150B, BR150L manufactured by Ube Industries, Ltd., BR730 manufactured by JSR Corporation, etc. When high cis BR is compounded, low temperature characteristics and wear resistance can be improved. Examples of rare earth BR include, for example, BUNA-CB25 manufactured by LANXESS, etc.

[0080] Examples of SPB-containing BR include those in which 1,2-syndiotactic polybutadiene crystals are chemically bonded to and dispersed in BR, but do not include those in which crystals are simply dispersed in BR. Examples of such SPB-containing BR include VCR-303, VCR-412, VCR-617, etc. manufactured by Ube Industries, Ltd.

[0081] Examples of modified BR include those obtained by adding a tin compound after polymerization of 1,3-butadiene by a lithium initiator (the terminal of which is further bonded by a tin-carbon bond (tin-modified BR)), butadiene rubber having an alkoxysilane compound condensed at the active end, etc. Examples of such modified BR include, for example, BR1250H (tin-modified) manufactured by ZS Elastomer Co., Ltd., S-modified polymers (modified for silica), etc.

[0082] The weight average molecular weight (Mw) of BR is preferably 300,000 or more, more preferably 350,000 or more, and further preferably 400,000 or more, from the perspective of wear resistance and grip performance. From the perspective of crosslinking uniformity, Mw is preferably 2,000,000 or less, and more preferably 1,000,000 or less. In addition, Mw can be calculated based on the measured value obtained by gel permeation chromatography (GPC) (e.g., GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, chromatographic column: TSKGELSUPERMULTIPORE HZ-M manufactured by Tosoh Corporation) using standard polystyrene.

[0083] In view of abrasion resistance, the content of BR in the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. In view of wet grip performance, the content is preferably 40% by mass or less, more preferably 35% by mass or less, further preferably 30% by mass or less, and particularly preferably 25% by mass or less.

[0084] The total content of SBR and BR in the rubber component is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 80% by mass or more, particularly preferably 85% by mass or more.

[0085] (Other rubber components)

[0086] As the rubber component of the present disclosure, the rubber component other than the above-mentioned SBR and BR can be compounded. As other rubber components, crosslinkable rubber components commonly used in the rubber industry can be used, such as isoprene-based rubber, styrene-isoprene-butadiene copolymer rubber (SIBR), styrene-isobutylene-styrene block copolymer (SIBS), chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), butyl rubber (IIR), ethylene-propylene rubber, polynorbornene rubber, silicone rubber, polyvinyl chloride rubber, fluororubber (FKM), acrylic rubber (ACM), polyepichlorohydrin rubber, etc. These other rubber components can be used alone or in combination of two or more.

[0087] As the isoprene-based rubber, for example, those commonly used in the tire industry, such as isoprene rubber (IR) and natural rubber, can be used. Examples of natural rubber include: unmodified natural rubber (NR); and modified natural rubbers, such as epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), deproteinized natural rubber (DPNR), ultrapure natural rubber (UPNR) and grafted natural rubber, etc. These rubbers can be used alone or in combination of two or more.

[0088] The NR is not particularly limited, and those commonly used in the tire industry can be used, and examples include, for example, SIR20, RSS#3, TSR20, and the like.

[0089] In this specification, "the total styrene content in styrene-butadiene rubber and butadiene rubber" means a value obtained by multiplying the styrene content of SBR by the SBR content relative to the total content of SBR and BR (SBR / (SBR+BR)). In the rubber component of the present disclosure, wet grip performance can be improved by setting the total styrene content in styrene-butadiene rubber and butadiene rubber to 25% by mass or more, preferably 26.5% by mass or more, more preferably 28% by mass or more, further preferably 30% by mass or more, and particularly preferably 32% by mass or more. On the other hand, the total styrene content in styrene-butadiene rubber and butadiene rubber is preferably 55% by mass or less, more preferably 50% by mass or less, and further preferably 45% by mass or less.

[0090] (Carbon Black)

[0091] Carbon black is not particularly limited, and those commonly used in the tire industry, such as GPF, FEF, HAF, ISAF and SAF, can be used. Specifically, N110, N115, N120, N125, N134, N135, N219, N220, N231, N234, N293, N299, N326, N330, N339, N343, N347, N351, N356, N358, N375, N539, N550, N582, N630, N642, N650, N66, 75, N66, 77N6727, N787, N907, N908, N990, N991, etc. can be appropriately used, and internal synthetic products can also be appropriately used. These can be used alone or in combination of two or more.

[0092] For weather resistance and reinforcement considerations, the nitrogen adsorption specific surface area (N 2 SA) is preferably 50m 2 / g or more, more preferably 80m 2 / g or more, more preferably 100m 2 / g or more. In addition, for the consideration of dispersibility, fuel efficiency, fracture characteristics and durability, N 2 SA is preferably 250m 2 / g or less, more preferably 220m 2 / g or less. In addition, N of carbon black in this specification is 2 SA is a value measured according to JIS K 6217-2:2017 “Carbon black for rubber industry - Basic properties - Part 2: Determination of specific surface area - Nitrogen adsorption method - Single point method” Method A.

[0093] In consideration of weather resistance and reinforcement, the content of carbon black is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 5 parts by mass or more relative to 100 parts by mass of the rubber component. In addition, in consideration of fuel efficiency, the content is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and further preferably 20 parts by mass or less.

[0094] (Silicon Dioxide)

[0095] When the rubber composition for tread of the present disclosure includes silica, fuel efficiency, wear resistance and wet grip performance can be improved. Silica is not particularly limited, and those commonly used in the tire industry can be used, such as silica prepared by dry method (anhydrous silica) and silica prepared by wet method (hydrous silica). Among these, hydrous silica prepared by wet method is preferred because it has many silanol groups. Silica can be used alone or in combination of two or more.

[0096] For the consideration of elongation at break, the nitrogen adsorption specific surface area (N 2 SA) is preferably 150m 2 / g or more, more preferably 180m 2 / g or more, more preferably 200m 2 / g or more. In addition, for fuel efficiency and processability considerations, N 2 SA is preferably 300m 2 / g or less, more preferably 250m 2 In addition, the BET specific surface area of ​​silica in this specification is a value measured by the BET method according to ASTM D3037-93.

[0097] The average primary particle size of silica is preferably less than 20nm, more preferably less than 14nm, and further preferably less than 12nm. The lower limit of the average primary particle size is not particularly limited, and is preferably more than 1nm, more preferably more than 3nm, and more preferably more than 5nm. When the average primary particle size of silica is within the above range, the dispersibility of silica can be further improved, and the reinforcement, fracture characteristics and wear resistance can be further improved. In addition, the average primary particle size of silica can be calculated as follows: observe silica with a transmission or scanning electron microscope, measure more than 400 silica primary particles observed in the field of view, and average them.

[0098] Relative to 100 parts by mass of the rubber component, when the content of silica is C (parts by mass) and the average primary particle size of silica is D (nm), C / D is preferably 3.8 or more. When C / D is 3.8 or more, the uneven wear resistance can be improved. C / D is more preferably 4.0 or more, further preferably 4.5 or more, and particularly preferably 4.8 or more. On the other hand, the upper limit of C / D can be, but is not particularly limited to, for example, less than 20, less than 15, less than 12, less than 10 or less than 8.0.

[0099] In view of fuel efficiency, wet grip performance and wear resistance, the content of silica when compounded is preferably 50 parts by mass or more, preferably 55 parts by mass or more, and more preferably 60 parts by mass or more relative to 100 parts by mass of the rubber component. In addition, in view of suppressing the deterioration of fuel efficiency and wear resistance caused by the deterioration of dispersibility of silica in rubber, the content is preferably 150 parts by mass or less, preferably 120 parts by mass or less, and more preferably 100 parts by mass or less.

[0100] (Other reinforcing fillers)

[0101] As reinforcing fillers other than carbon black and silica, those commonly used in the conventional tire industry, such as aluminum hydroxide, calcium carbonate, alumina, clay, and talc, may be compounded.

[0102] (Silane coupling agent)

[0103] Preferably, the silane coupling agent having a mercapto group is a compound represented by the following formula (3) and / or a compound comprising a bonding unit A represented by the following formula (4) and a bonding unit B represented by the following formula (5).

[0104]

[0105] (Where R 101 , R 102 and R 103 Each independently represents the following group: C 1 -C 12 Alkyl, C 1 -C 12 Alkoxy or -O-(R 111 -O) z -R 112 (z R 111 Each independently represents C 1 -C 30 Divalent hydrocarbon group; R 112 Represents C 1 -C 30 Alkyl, C 2 -C 30 Alkenyl, C 6 -C 30 Aryl or C 7 -C 30 aralkyl; z represents an integer from 1 to 30); R 104 Represents C 1 -C 6 Alkylene.)

[0106]

[0107] (wherein, x represents an integer greater than 0; y represents an integer greater than 1; R 201 Represents C 1 -C 30 Alkyl, C 2 -C 30 Alkenyl or C 2 -C 30 Alkynyl, which may be substituted by a hydrogen atom, a halogen atom, a hydroxyl group or a carboxyl group; R 202 Represents C 1 -C 30 Alkylene, C 2 -C 30 Alkenylene or C 2 -C 30 Alkyne; wherein R 201 and R 202 Can form a ring structure together.)

[0108] Examples of the compound represented by formula (3) include: for example, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, a compound represented by the following formula (6) (Si363, manufactured by Evonik Degussa AG), etc., and the compound represented by the following formula (6) can be appropriately used.

[0109] These may be used alone or in combination of two or more.

[0110]

[0111] By using a compound comprising a bonding unit A represented by formula (4) and a bonding unit B represented by formula (5), the viscosity increase during processing is suppressed compared to a sulfide-based silane coupling agent such as bis-(3-triethoxysilylpropyl)tetrasulfide. As a result, silica dispersibility becomes better, and fuel efficiency, wet grip performance, and elongation at break tend to be further improved. It is believed that this is because the sulfide portion of the bonding unit A is a CSC bond and is therefore thermally stable compared to tetrasulfide or disulfide, resulting in a small increase in Mooney viscosity.

[0112] In view of suppressing the viscosity increase during processing, the content of the bonding unit A is preferably 30 mol% to 99 mol%, more preferably 50 mol% to 90 mol%. In addition, the content of the bonding unit B is preferably 1 mol% to 70 mol%, more preferably 5 mol% to 65 mol%, and further preferably 10 mol% to 55 mol%. In addition, the total content of the bonding units A and B is preferably 95 mol% or more, more preferably 98 mol% or more, and particularly preferably 100 mol%. In addition, the amount referred to by the content of the bonding units A and B includes the case where the bonding units A and B are located at the terminal of the silane coupling agent. The form in which the bonding units A and B are located at the terminal of the silane coupling agent is not particularly limited as long as it forms a bonding unit A corresponding to the bonding unit represented by formula (4) and a bonding unit B represented by formula (5).

[0113] In the compound comprising the bonding unit A represented by formula (4) and the bonding unit B represented by formula (5), the total repetition number (x+y) of the repetition number (x) of the bonding unit A and the repetition number (y) of the bonding unit B is preferably 3 to 300. Within this range, the mercaptosilane of the bonding unit B is replaced by the -C 7 H 15 The coating makes it possible to suppress the shortening of the scorch time and ensure good reactivity with silica and the rubber component.

[0114] Examples of the compound containing the bonding unit A represented by formula (4) and the bonding unit B represented by formula (5) include NXT-Z30, NXT-Z45, NXT-Z60 and NXT-Z100 manufactured by Momentive Performance Materials, Inc. These may be used alone or in combination of two or more.

[0115] In consideration of fuel efficiency, the content of the silane coupling agent having a mercapto group is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, further preferably 2 parts by mass or more, and particularly preferably 4 parts by mass or more, relative to 100 parts by mass of silica. In consideration of rubber strength and wear resistance, the content is preferably 20 parts by mass or less, more preferably 12 parts by mass or less, further preferably 10 parts by mass or less, and particularly preferably 9 parts by mass or less.

[0116] In the present disclosure, the rubber composition may further include other silane coupling agents in addition to the above-mentioned silane coupling agent having a mercapto group. Examples of other silane coupling agents include, for example, silane coupling agents having a sulfide group, such as bis(3-triethoxysilylpropyl)disulfide and bis(3-triethoxysilylpropyl)tetrasulfide; silane coupling agents having a vinyl group, such as vinyltriethoxysilane and vinyltrimethoxysilane; silane coupling agents having an amino group, such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents, such as γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents, such as 3-nitropropyltrimethoxysilane, 3-nitropropyltriethoxysilane; chlorine-based silane coupling agents, such as 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, and the like. These silane coupling agents may be used alone or in combination of two or more.

[0117] Preferably, the rubber composition for a tread of the present disclosure contains zinc dithiophosphate represented by the following formula (7):

[0118]

[0119] (Where R 1 , R 2 , R 3 and R 4 Each independently represents C 1 -C 18 Alkyl or C 5 -C 12 Cycloalkyl.)

[0120] During mixing, the mercapto group of the silane coupling agent having a mercapto group is easily radicalized and bonded to the polymer, resulting in gelation. When the rubber composition for the tread contains the above-mentioned zinc dithiophosphate, the radicalized mercapto group of the silane coupling agent reacts with the -S-Zn- structural part of the zinc dithiophosphate, and then reacts with the rubber component to form a disulfide bond. In other words, the free radical from the mercapto group is captured by the zinc dithiophosphate. Therefore, the reactivity of the silane coupling agent with the rubber component is reduced, and gelation can be suppressed. In addition, when the temperature rises during vulcanization, the disulfide bond breaks and reacts with the rubber component, thereby being able to play the role of a silane coupling agent.

[0121] As specific examples of zinc dithiophosphate, for example, TP-50, ZBOP-S, ZBOP-50 manufactured by Rhein Chemie and compounds similar thereto (for example, each R in formula (7) 1 , R 2 , R 3 and R 4 is a compound containing n-propyl, isopropyl or n-octyl) etc.

[0122] In the case of compounding zinc dithiophosphate, the content of zinc dithiophosphate is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and further preferably 0.5 parts by mass or more relative to 100 parts by mass of the rubber component. When the content of zinc dithiophosphate is 0.1 parts by mass or more, processability is improved, dispersibility of silica is further improved, and fuel efficiency, wet grip performance, and elongation at break tend to be further improved. In addition, from the perspective of breaking strength and wear resistance, the content is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and further preferably 3 parts by mass or less.

[0123] In the case of adding zinc dithiophosphate, the content of zinc dithiophosphate is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 5 parts by mass or more relative to 100 parts by mass of the silane coupling agent. When the content of zinc dithiophosphate is 1 part by mass or more, the processability is improved, the dispersibility of silica is further improved, and the fuel efficiency, wet grip performance and elongation at break tend to be further improved. In addition, from the perspective of breaking strength and wear resistance, the content is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 40 parts by mass or less.

[0124] In addition to the above components, the rubber composition for tread of the present disclosure may appropriately contain compounding agents commonly used in the conventional tire industry, such as oil, tackifying resin, wax, processing aid, antioxidant, softener, zinc oxide, stearic acid, vulcanizing agent (such as sulfur) and vulcanization accelerator.

[0125] Examples of the oil include, for example, mineral oils such as aromatic oils, process oils, paraffin oils, etc. Among these, process oils are preferably used because they reduce the burden on the environment.

[0126] In the case of compounding oil, the content of oil is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and further preferably 20 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of processability. In addition, from the viewpoint of wear resistance, the content is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and further preferably 60 parts by mass or less. In addition, in this specification, the content of oil also includes the amount of oil contained in the oil-extended rubber.

[0127] Examples of the tackifier resin include cyclopentadiene resins, coumarone resins, petroleum resins (aliphatic petroleum resins, aromatic petroleum resins, alicyclic petroleum resins, etc.), phenol resins, rosin derivatives, etc., and aromatic petroleum resins are preferred.

[0128] Examples of the aromatic petroleum resin include, for example, the following aromatic vinyl-based resins and C9-based petroleum resins other than aromatic vinyl-based resins, and the like, with preference given to aromatic vinyl-based resins.

[0129] The aromatic vinyl resin may include a homopolymer of an aromatic vinyl monomer (unit) and a copolymer of two or more aromatic vinyl monomers, including, for example, styrene, α-methylstyrene, 1-vinylnaphthalene, 3-vinyltoluene, ethylvinylbenzene, divinylbenzene, 4-cyclohexylstyrene, 2,4,6-trimethylstyrene, etc. In addition, those obtained by modifying them can be used.

[0130] As the aromatic vinyl resin, α-methylstyrene or a homopolymer of styrene or a copolymer of α-methylstyrene and styrene is preferred, and a copolymer of α-methylstyrene and styrene is more preferred (because it is economical, easy to process and has excellent wet grip performance). As the aromatic vinyl resin, commercially available products such as SYLVARESSA85, SA100, SA120, SA140 manufactured by Kraton and R2336 manufactured by Eastman Chemical Company can be appropriately used. As the copolymer of α-methylstyrene and styrene, for example, SYLVATRAXX4401 manufactured by Kraton can be appropriately used.

[0131] The softening point of the tackifier resin is preferably 40°C or higher, more preferably 60°C or higher. When the softening point is 40°C or higher, sufficient grip performance tends to be obtained. In addition, the softening point is preferably 120°C or lower, more preferably 100°C or lower. When the softening point is 120°C or lower, sufficient grip performance tends to be obtained. In addition, the softening point of the resin in this specification refers to the temperature when a ball falls when the softening point specified in JIS K6220-1:2001 is measured using a ring and ball softening point measuring device.

[0132] When a tackifier resin is compounded, the content of the tackifier resin (particularly an aromatic vinyl resin) is preferably 1 part by mass or more, more preferably 2 parts by mass or more, further preferably 3 parts by mass or more, and particularly preferably 4 parts by mass or more relative to 100 parts by mass of the rubber component in consideration of wet grip performance. In addition, in consideration of fuel efficiency and wear resistance, the content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, further preferably 35 parts by mass or less, and particularly preferably 10 parts by mass or less.

[0133] Examples of processing aids include, for example, fatty acid metal salts, fatty acid amides, amide esters, silicon dioxide surfactants, fatty acid esters, mixtures of fatty acid metal salts and amide esters, mixtures of fatty acid metal salts and fatty acid amides, etc. They can be used alone or in combination of two or more. Among these, preferred fatty acid metal salts, amide esters, mixtures of fatty acid metal salts and amide esters, mixtures of fatty acid metal salts and fatty acid amides, particularly preferred mixtures of fatty acid metal salts and fatty acid amides. Specifically, examples of processing aids include, for example, fatty acid soap-based processing aids, such as EF44 and WB16 manufactured by Schill+Seilacher.

[0134] When a processing aid is compounded, the content of the processing aid is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the rubber component, in order to exhibit an effect of improving processability. In addition, in consideration of wear resistance and breaking strength, the content is preferably 10 parts by mass or less, more preferably 8 parts by mass or less.

[0135] Examples of antioxidants include, but are not particularly limited to, for example, amine antioxidants, quinoline antioxidants, quinone antioxidants, phenol antioxidants, and imidazole antioxidants, as well as antioxidants such as metal carbamates. Among these, preferred are phenylenediamine antioxidants, such as N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, N-cyclohexyl-N'-phenyl-p-phenylenediamine, N,N'-bis(1-methylheptyl)-p-phenylenediamine, N,N'-bis(1,4-dimethylpentyl)-p-phenylenediamine, diamine, N,N'-bis(1-ethyl-3-methylpentyl)-p-phenylenediamine, N-4-methyl-2-pentyl-N'-phenyl-p-phenylenediamine, N,N'-diaryl-p-phenylenediamine, hindered diaryl-p-phenylenediamine, phenylhexyl-p-phenylenediamine, phenyloctyl-p-phenylenediamine; and quinoline antioxidants, such as 2,2,4-trimethyl-1,2-dihydroquinoline polymers and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline. Among these, quinoline antioxidants are more suitable for use due to heat resistance. These antioxidants can be used alone or in combination of two or more.

[0136] When an antioxidant is compounded, the content of the antioxidant is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the rubber component, in consideration of the ozone cracking resistance of the rubber. In addition, in consideration of abrasion resistance and wet grip performance, the content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.

[0137] When wax is compounded, the wax content is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the rubber component, in consideration of the weather resistance of the rubber. In addition, in consideration of whitening of the tire due to blooming, the wax content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.

[0138] When stearic acid is blended, the content of stearic acid is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the rubber component, for processability considerations. In addition, for vulcanization speed considerations, the content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.

[0139] When zinc oxide is compounded, the content of zinc oxide is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the rubber component, from the perspective of processability. In addition, from the perspective of wear resistance, the content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.

[0140] Sulfur is suitably used as a vulcanizing agent. As sulfur, powdered sulfur, process oil sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, etc. can be used.

[0141] In the case of compounding sulfur as a vulcanizing agent, the content of sulfur is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, relative to 100 parts by mass of the rubber component, in order to ensure sufficient vulcanization reaction and obtain good grip performance and wear resistance. In addition, from the perspective of performance deterioration, the content is preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and further preferably 2.0 parts by mass or less. In addition, when oil-containing sulfur is used as a vulcanizing agent, the content of the vulcanizing agent should be the total content of pure sulfur contained in the oil-containing sulfur.

[0142] Examples of the vulcanizing agent other than sulfur include, for example, a sulfur atom-containing vulcanizing agent such as TACKIROL V200 manufactured by Taoka Chemical Co., Ltd., DURALINK HTS (sodium hexamethylene-1,6-dithiosulfate dihydrate) manufactured by Flexex, KA9188 (1,6-bis(N,N'-dibenzylthiocarbamoyldisulfide)hexane) manufactured by LANXESS; an organic peroxide such as dicumyl peroxide, and the like.

[0143] Examples of the vulcanization accelerator include, but are not particularly limited to, for example, sulfenamide vulcanization accelerators, thiazole vulcanization accelerators, thiuram vulcanization accelerators, thiourea vulcanization accelerators, guanidine vulcanization accelerators, dithiocarbamic acid vulcanization accelerators, aldehydeamine or aldehydeamine vulcanization accelerators, imidazoline vulcanization accelerators, xanthate vulcanization accelerators; among these, sulfenamide vulcanization accelerators and / or thiuram vulcanization accelerators are preferred, and a combination of the two is more preferred, from the viewpoint that the desired effect can be more appropriately obtained.

[0144] Examples of sulfenamide-based vulcanization accelerators include CBS (N-cyclohexyl-2-benzothiazole sulfenamide), TBBS (N-tert-butyl-2-benzothiazole sulfenamide), N-oxyethylene-2-benzothiazole sulfenamide, N,N'-diisopropyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, etc. Examples of thiazole-based vulcanization accelerators include 2-mercaptobenzothiazole, dibenzothiazole disulfide, etc. Examples of thiuram-based vulcanization accelerators include tetramethylthiuram monosulfide, tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), tetra(2-ethylhexyl)thiuram disulfide (TOT-N), etc. Examples of guanidine-based vulcanization accelerators include diphenylguanidine (DPG), di-o-tolylguanidine, o-tolylbiguanide, etc. These may be used alone or in combination of two or more. Among these, a combination of CBS and TBzTD is particularly preferred because the desired effect can be more appropriately obtained.

[0145] The total content of the vulcanization accelerator is preferably 1.0 parts by mass or more, more preferably 1.5 parts by mass or more, and further preferably 2.0 parts by mass or more, relative to 100 parts by mass of the rubber component. In addition, the total content of the vulcanization accelerator is preferably 8.0 parts by mass or less, more preferably 7.0 parts by mass or less, further preferably 6.0 parts by mass or less, and particularly preferably 5.0 parts by mass or less, relative to 100 parts by mass of the rubber component. When the content of the vulcanization accelerator is within the above range, the breaking strength and elongation tend to be ensured.

[0146] When a thiuram vulcanization accelerator is compounded, the content of the thiuram vulcanization accelerator is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the rubber component, from the viewpoint of fuel efficiency and handling stability. Furthermore, from the viewpoint of handling stability, the content is preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, further preferably 1.0 parts by mass or less, and particularly preferably 0.8 parts by mass or less.

[0147] The rubber composition of the present disclosure can be manufactured by known methods. For example, it can be manufactured by the following method: with a known kneading machine (e.g., Banbury mixer, kneading machine, open roll mill) commonly used in the rubber industry, the above-mentioned ingredients except the vulcanizing agent and the vulcanization accelerator are kneaded, and then the vulcanizing agent and the vulcanization accelerator are added to the mixture for further kneading, and then vulcanization, etc.

[0148] Since the tread surface temperature at the head of the tire shoulder reaches 80°C to 120°C during high-speed driving, it is necessary to improve the tensile properties of the tread rubber at high temperatures to suppress uneven wear. The elongation at break EB of the rubber composition disclosed herein measured under the conditions of an atmosphere of 100°C and a tensile rate of 14.0 m / s is preferably 180% or more, more preferably 190% or more, further preferably 200% or more, further preferably 210% or more, further preferably 220% or more, further preferably 225% or more, further preferably 230% or more, and particularly preferably 240% or more. When the elongation at break is within the above range, uneven wear caused by the increase in the tread surface temperature at the head of the tire shoulder can be suppressed. In addition, the elongation at break in the present disclosure is measured as follows: the vulcanized rubber composition is made into a dumbbell-shaped test piece No. 7, and a tensile test is performed according to JIS K 6251:2017 "Vulcanized or thermoplastic rubber-Determination of tensile stress-strain properties".

[0149] <Tires>

[0150] The pneumatic tire of the present disclosure has a tread composed of the above-mentioned rubber composition for tread, and is suitably used for tires for passenger cars, high-performance tires for passenger cars, and the like.

[0151] A tire having a tread (made of the above-mentioned rubber composition for tread) can be manufactured by a conventional method using the above-mentioned rubber composition for tread. In other words, the tire can be manufactured by extruding an unvulcanized rubber composition compounded from a rubber component and other necessary components into a tread shape, attaching it to a tire molding machine together with other tire components, molding them by a conventional method to form an unvulcanized tire, and then heating and pressurizing the unvulcanized tire in a vulcanizer.

[0152] Figure 1 A schematic diagram of a cut section when the tread is pressed against a flat surface is shown. The aspect ratio of the pneumatic tire of the present disclosure is 35% to 70%, wherein Y is defined by the following formula:

[0153] Y=(B-16) / A

[0154] Wherein, when the tread of the tire (the tire is mounted on a normal rim by the rim and is in a normal state with normal internal pressure and no load) is pressed on a flat surface under the application of normal load, A is the total width of the tire (mm), B is the width of the buffer layer of the tire (mm), when the aspect ratio is greater than 35% and less than 40%, Y is less than 0.80 (preferably less than 0.79, more preferably less than 0.78); when the aspect ratio is greater than 40% and less than 45%, Y is less than 0.79 (preferably less than 0.78, more preferably less than 0.77); when the aspect ratio is greater than 45% and less than 50%, Y is less than 0.78 (preferably less than 0.77, more preferably less than 0.76); when When the aspect ratio is 50% or more and less than 55%, Y is 0.77 or less (preferably 0.76 or less, more preferably 0.75 or less); when the aspect ratio is 55% or more and less than 60%, Y is 0.75 or less (preferably 0.74 or less, more preferably 0.73 or less); when the aspect ratio is 60% or more and less than 65%, Y is 0.72 or less (preferably 0.71 or less, more preferably 0.70 or less); when the aspect ratio is 65% or more and less than 70%, Y is 0.69 or less (preferably 0.68 or less, more preferably 0.67 or less); or when the aspect ratio is 70%, Y is 0.67 or less (preferably 0.66 or less, more preferably 0.65 or less). In this way, by adjusting the total width of the tire and the width of the buffer layer of the tire, it is possible to suppress eccentric wear and avoid premature detachment of the tire due to eccentric wear, thereby fully demonstrating the inherent wear resistance of the rubber composition for the tread.

[0155] In the pneumatic tire disclosed herein, by setting Y to be below the above-mentioned predetermined value, wear resistance and fuel efficiency can be improved. On the other hand, when Y exceeds the above-mentioned predetermined value, in particular, fuel efficiency tends to deteriorate. On the other hand, the lower limit value of Y is not particularly limited, and is generally above 0.50, preferably above 0.55, more preferably above 0.58, and further preferably above 0.60. In addition, the lower limit value of Y corresponding to each of the above-mentioned flatness rates is preferably 0.20 less than the upper limit value of Y corresponding to each of the above-mentioned flatness rates, more preferably 0.15 less than, and further preferably 0.10 less than. For example, when the flatness rate is greater than 35% and less than 40%, Y can be 0.60 to 0.80, 0.65 to 0.80, 0.70 to 0.80, 0.59 to 0.79, 0.64 to 0.79, 0.69 to 0.79, 0.58 to 0.78, 0.63 to 0.78, or 0.68 to 0.78.

[0156] The aspect ratio of the pneumatic tire disclosed herein is not particularly limited as long as it is in the range of 35% to 70%, for example, it can be 35% to 65%, 35% to 60%, 35% to 55%, 40% to 70%, 45% to 70% or 50% to 70%.

[0157] The "normal rim" is the rim of each tire defined by the standard in the standard system on which the tire is based. For example, it is the "standard rim" in JATMA, the "design rim" in TRA, or the "measurement rim" in ETRTO. In addition, if the tire size is not specified in the above standard system, the normal rim is the rim with the narrowest width among the rims with the smallest diameter that can be fitted to the tire without causing air leakage between the rim and the tire.

[0158] "Normal internal pressure" is the air pressure of each tire defined by the standard, i.e., the "maximum air pressure" in JATMA, the maximum value described in the table "Tire load limits at various cold inflation pressures" of TRA, or the "inflation pressure" in ETRTO. In addition, if the tire size is not specified in the above standard system, the normal internal pressure should be 250kPa.

[0159] The "normal state" is a state where the tire is mounted on a normal rim, filled with normal internal pressure, and no load is applied. In addition, when the tire size is not specified in the above standard system, the normal state is a state where the tire is mounted on the smallest rim, filled with 250 kPa, and no load is applied.

[0160] "Normal load" is the load of each tire defined by the standard, i.e., the maximum load capacity in JATMA, the maximum value described in the table "Tire load limits at various cold inflation pressures" of TRA, or "Load capacity" of ETRTO. In addition, when the tire size is not specified in the above standard system, the normal load W can be estimated by the following equations (1) and (2): L (kg), where W t (mm) is the tire section width measured under normal conditions, H t (mm) is the tire section height measured under normal conditions, D t (mm) is the outer diameter of the tire measured under normal conditions. The cross-sectional width W of the tire t It is the maximum width between the outer surfaces of the sidewalls excluding the patterns or characters on the tire side in the above state. Tire section height H t It is the distance from the bottom of the bead part to the outermost surface of the tread, which is half the difference between the outer diameter of the tire and the nominal size of the rim.

[0161] V={(D t / 2) 2 -(D t / 2-H t ) 2}×π×W t (1)

[0162] W L =0.000011×V+175 (2)

[0163] The value of Y can be obtained by appropriately using and adjusting methods (such as mold profile, specification distribution and configuration), but the adjustment method is not particularly limited. For example, the desired values ​​of A and B can be obtained by adjusting the width of the buffer layer or the width of the mold. Specifically, Y can be adjusted to a larger value by increasing the width of the buffer layer or reducing the width of the mold, while Y can be adjusted to a smaller value by reducing the width of the buffer layer or increasing the width of the mold.

[0164] The tread of the present invention has at least one rubber layer. The tread of the present invention may be formed of a single rubber layer, or may have one or more rubber layers on the tire radially inner side of the rubber layer (running surface rubber layer) constituting the tread surface on the outer surface. When the tread of the present invention is composed of two or more rubber layers, at least one of the two or more rubber layers is composed of the above-mentioned predetermined rubber composition, and preferably, the tread cap rubber layer is composed of the above-mentioned predetermined rubber composition.

[0165] Example

[0166] Hereinafter, the present disclosure will be described based on embodiments, but the present disclosure is not limited to these embodiments.

[0167] Various chemicals used in Examples and Comparative Examples are collectively shown below.

[0168] SBR1: modified solution-polymerized SBR synthesized in Production Example 1 described below (styrene content: 35% by mass, vinyl bond amount: 34 mol%, Mw: 850,000, Tg: -30°C, oil-extended product, containing 37.5 parts by mass of oil content (relative to 100 parts by mass of the rubber component));

[0169] SBR2: modified solution-polymerized SBR produced in Production Example 2 described below (styrene content: 38 mass %, vinyl bond amount: 39 mol %, Mw: 800,000, Tg: -25°C, oil-extended product, containing 25 parts by mass of oil content (relative to 100 parts by mass of the rubber component));

[0170] SBR3: modified solution-polymerized SBR produced in Production Example 3 described below (styrene content: 42 mass %, vinyl bond amount: 36 mol %, Mw: 800,000, Tg: -21°C, oil-extended product, containing 10 parts by mass of oil content (relative to 100 parts by mass of the rubber component));

[0171] SBR4: modified solution-polymerized SBR prepared in Production Example 4 described below (styrene content: 30% by mass, vinyl bond amount: 52 mol%, Mw: 250,000, Tg: -23°C, non-oil-extended product);

[0172] BR: Ubepol BR (registered trademark) 150B manufactured by Ube Industries, Ltd. (vinyl bond content: 1.5 mol%, cis-1,4 bond content: 97%, Mw: 440,000);

[0173] NR:TSR20;

[0174] Carbon black: DIABLACK N220 (N 2 SA: 115m 2 / g);

[0175] Silica 1: Zeosil Premium 200MP (N 2 SA: 220m 2 / g, average primary particle size: 15nm);

[0176] Silicon dioxide 2: Ultrasil (registered trademark) 9100GR (N 2 SA: 230m 2 / g, average primary particle size: 15nm);

[0177] Silicon dioxide 3: Ultrasil (registered trademark) VN3 (N 2 SA: 175m 2 / g, average primary particle size: 18nm);

[0178] Silane coupling agent 1: NXT-Z45 manufactured by Momentive High Performance Materials (a silane coupling agent having a mercapto group, a copolymer of a bonding unit A and a bonding unit B (bonding unit A: 55 mol%, bonding unit B: 45 mol%));

[0179] Silane coupling agent 2: Si69 (bis(3-triethoxysilylpropyl)tetrasulfide) manufactured by Evonik Degussa;

[0180] Oil: VivaTec 400 (TDAE oil) produced by H&R Group;

[0181] Tackifying resin: Sylvatraxx (registered trademark) 4401 manufactured by Kraton (copolymer of α-methylstyrene and styrene, softening point: 85° C.);

[0182] Wax: OZOACE 0355 manufactured by Nippon Seira Co., Ltd.

[0183] Antioxidant 1: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) produced by Ouchi Shinko Chemical Industry Co., Ltd.;

[0184] Antioxidant 2: Nocrac FR (2,2,4-trimethyl-1,2-dihydroquinoline polymer) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.;

[0185] Processing aid: STRUKTOL EF44 (fatty acid zinc) manufactured by Xilun Selehe Company;

[0186] Stearic acid: beaded stearic acid "CAMELLIA" manufactured by NOF Corporation;

[0187] Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining and Smelting Co., Ltd.;

[0188] Zinc dithiophosphate: TP-50 manufactured by Rhein Chemie (compound represented by formula (7), R1 to R4: n-butyl, active ingredient content: 50% by mass);

[0189] Sulfur: HK-200-5 (powdered sulfur containing 5% oil) manufactured by Hosoi Chemical Industry Co., Ltd.

[0190] Vulcanization accelerator 1: Nocceler CZ (N-cyclohexyl-2-benzothiazole sulfenamide (CBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.;

[0191] Vulcanization accelerator 2: Sanceler TBZTD (tetrabenzylthiuram disulfide (TBzTD)) manufactured by Sanshin Chemical Industry Co., Ltd.

[0192] Production Example 1: Synthesis of SBR1

[0193] A nitrogen purged autoclave reactor (internal volume 20 L) with a stirrer and a jacket was subjected to a nitrogen purge, and the temperature was controlled at 70°C. Styrene, 1,3-butadiene (containing 100 ppm of 1,2-butadiene), cyclohexane, tetrahydrofuran and n-butyl lithium were added at a rate of 10.5 g / min, 19.5 g / min, 150 g / min, 1.5 g / min and 0.117 mmol / min, respectively. Silicon tetrachloride was continuously added at a rate of 0.04 mmol / min at the top outlet of the first reaction vessel, and introduced into a second reaction vessel connected to the first reaction vessel for modification reaction. After the polymerization reaction was completed, 2,6-di-tert-butyl-p-cresol was added to the polymer solution. Next, after adding 37.5 parts by mass (relative to 100 parts by mass of polymer) of filler oil (VivaTec 400 manufactured by H&R Group), the mixture was stripped to remove the solvent and dried with a heated roller (temperature adjusted to 110°C) to obtain SBR1.

[0194] Production Example 2: Synthesis of SBR2

[0195] Two autoclaves with an inlet at the bottom and an outlet at the top and equipped with a stirrer and a jacket are connected in series as a reactor (internal volume 10L), and butadiene, styrene and cyclohexane are mixed in a predetermined ratio under a nitrogen atmosphere. After mixing n-butyl lithium with a static mixer to remove impurities, the mixed solution is continuously supplied from the bottom of the first reactor to pass through a dehydration tower equipped with activated alumina, and then 2,2-bis(2-oxolane)propane and n-butyl lithium as polar substances and polymerization initiators, respectively, are continuously supplied from the bottom of the first reactor at a predetermined rate, and the temperature in the reactor is maintained at 95°C. The polymer solution is continuously extracted from the top of the reactor and supplied to the second reactor. The temperature of the second reactor is maintained at 95°C, and a mixture of tetraglycidyl-1,3-bisaminomethylcyclohexane (monomer) as a modifier and an oligomer component is continuously added as a 1000-fold cyclohexane dilution solution at a predetermined rate to carry out a modification reaction. The polymer solution is continuously extracted from the reactor, and 2,6-di-tert-butyl-p-cresol is continuously added with a static mixer. Next, 25 parts by mass (per 100 parts by mass of the polymer) of extender oil (NC-140 manufactured by JXTG Nippon Oil & Energy Co., Ltd.) was added, the solvent was removed by steam stripping, and the mixture was dried using a heating roll (adjusted to 110° C.) to obtain SBR2.

[0196] Production Example 3: Synthesis of SBR3

[0197] Cyclohexane, tetrahydrofuran, styrene and 1,3-butadiene were charged into an autoclave reactor purged with nitrogen. After the temperature of the materials in the reactor was adjusted to 20°C, n-butyl lithium was added to initiate the polymerization reaction. The polymerization was carried out under adiabatic conditions, and the temperature reached a maximum temperature of 85°C. When the polymerization conversion reached 99%, 1,3-butadiene was added, and after polymerizing for another 5 minutes, N,N-bis(trimethylsilyl)-3-aminopropyltrimethoxysilane was added as a modifier for reaction. After the polymerization reaction was completed, 2,6-di-tert-butyl-p-cresol was added. Next, after adding 10 parts by mass of filler oil (relative to 100 parts by mass of polymer), the solvent was removed by steam stripping, and dried by a heated roller (the temperature was adjusted to 110°C) to obtain SBR3.

[0198] Production Example 4: Synthesis of SBR4

[0199] Cyclohexane, tetrahydrofuran, styrene and 1,3-butadiene were charged into an autoclave reactor purged with nitrogen. After the temperature of the materials in the reactor was adjusted to 20°C, n-butyl lithium was added to initiate the polymerization reaction. The polymerization was carried out under adiabatic conditions, and the temperature reached a maximum temperature of 85°C. When the polymerization conversion rate reached 99%, 1,3-butadiene was added, and after another 5 minutes of polymerization, N,N-bis(trimethylsilyl)-3-aminopropyltrimethoxysilane was added as a modifier for reaction. After the polymerization reaction was completed, 2,6-di-tert-butyl-p-cresol was added. Then, the mixture was stripped to remove the solvent and dried by a heated roller (the temperature was adjusted to 110°C) to obtain SBR4.

[0200] (Examples and Comparative Examples)

[0201] According to the compounding formula shown in Tables 1 to 3, all chemicals except sulfur and vulcanization accelerator were kneaded to a discharge temperature of 150°C to 160°C for 1 to 10 minutes using a 1.7L closed Banbury mixer to obtain a kneaded product. Then, sulfur and vulcanization accelerator were added to the obtained kneaded product using a twin-screw open roll mill, and kneaded for 4 minutes until the temperature reached 105°C to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was press-vulcanized at 170°C for 12 minutes to prepare a test rubber composition.

[0202] In addition, the unvulcanized rubber composition was extruded into a tire tread shape using an extruder equipped with a suction nozzle of a predetermined shape and connected together with other tire components to form an unvulcanized tire. The unvulcanized tire was pressurized and vulcanized at 170° C. for 12 minutes to prepare test tire 1 (size: 205 / 55R16, rim: 16×7.0, internal pressure: 250 kPa), test tire 2 (size: 185 / 70R14, rim: 14×5.5, internal pressure: 250 kPa) and test tire 3 (size: 255 / 35R18, rim: 18×9.0, internal pressure: 250 kPa).

[0203] The obtained test rubber compositions and test tires were evaluated as follows. Table 1 shows the evaluation results of test tire 1 (aspect ratio: 55%), Table 2 shows the evaluation results of test tire 2 (aspect ratio: 70%), and Table 3 shows the evaluation results of test tire 3 (aspect ratio: 35%).

[0204] <Elongation at break>

[0205] A No. 7 dumbbell-shaped test piece composed of each vulcanized rubber composition was prepared, and a tensile test was carried out in an atmosphere of 100°C at a tensile rate of 14.0 m / s according to JIS K 6251:2017 "Rubber, vulcanized or thermoplastic - Determination of tensile stress-strain properties" to measure the elongation at break (elongation at break) EB (%).

[0206] <Fuel Efficiency (Laboratory)>

[0207] Strip specimens with a width of 4 mm, a length of 50 mm, and a thickness of 2 mm were punched out from the sheet-like vulcanized rubber composition and tested. The loss tangent (tanδ) of the vulcanized rubber sheet was measured using a spectrometer manufactured by Ueshima Seisakusho at a dynamic strain amplitude of 1%, a frequency of 10 Hz, and a temperature of 50°C. The reciprocal value of tanδ is displayed as an index, with the reference comparative example (Comparative Example 1 in Table 1, Comparative Example 7 in Table 2, and Comparative Example 10 in Table 3, the same below) being 100. The larger the value, the smaller the rolling resistance and the better the fuel efficiency.

[0208] (Fuel efficiency index (laboratory)) = (Tan δ of reference comparative example) / (Tan δ of each compounding example) × 100

[0209] <Fuel efficiency (tires)>

[0210] For each test tire, the rolling resistance coefficient (RRC) was measured according to JIS D 4234:2009 (ISO 28580), and the reciprocal of the rolling resistance coefficient was expressed as an index, with the reference comparative example in each table being 100. The larger the index, the smaller the rolling resistance and the better the fuel efficiency.

[0211] (Fuel efficiency index (tire)) = (rolling resistance coefficient of reference comparative example) / (rolling resistance coefficient of each test tire) × 100

[0212] <Wet Grip Performance (Laboratory)>

[0213] The wet grip performance was evaluated using a flat belt wear tester (FR5010 model) manufactured by Ueshima Manufacturing Co., Ltd. A cylindrical rubber specimen with a width of 20 mm and a diameter of 100 mm of each vulcanized rubber composition was used as a sample. Under the conditions of a speed of 20 km / h, a load of 4 kgf, and a road surface temperature of 20°C, the slip rate of the sample relative to the road surface changed from 0% to 70%, and the maximum value of the friction coefficient detected at that time was read. Then, the measurement results are displayed as an index by the following equation. The larger the index, the larger the friction coefficient, and the more excellent the wet grip performance.

[0214] (Wet Grip Performance Index (Laboratory)) = (Maximum Friction Coefficient of Each Compounding Example) / (Maximum Friction Coefficient of Reference Comparative Example) × 100

[0215] <Wet grip performance (actual vehicle)>

[0216] Each test tire was mounted on all wheels of a vehicle (FF2000cc made in Japan), and the braking distance from an initial speed of 100 km / h was measured on a wet asphalt road surface and displayed as an index, with the reference comparative example in each table being 100. The larger the index, the shorter the braking distance and the more excellent the wet grip performance.

[0217] (Wet grip performance index (actual vehicle)) = (braking distance of reference comparative example) / (braking distance of each test tire) × 100

[0218] <Handling stability at high speeds>

[0219] Each test tire was mounted on a 2000cc Japanese-made FR vehicle. The vehicle was driven on a test route on a dry asphalt road at a speed of about 120 km / h, and the handling characteristics during straight driving, lane change, and acceleration / deceleration were evaluated by sensory evaluation of the test driver. The evaluation results are shown as an index, with the handling characteristics of the reference comparative example in each table being 100, and the average of the above three cases being calculated according to the following criteria, and its index value is shown in the "Handling Stability" column in Tables 1 to 3. The larger the index value, the better the handling characteristics and the more excellent the handling stability during high-speed driving.

[0220] (Standards for handling characteristics)

[0221] 120: Better than ever before

[0222] 110: Test driver judgment performance significantly improved

[0223] 105: Test driver felt slightly improved

[0224] 100: Standard

[0225] 90: Feels slightly below standard

[0226] 80: Test driver judgment performance deteriorated significantly

[0227] <Uneven wear resistance during high-speed driving>

[0228] Each test tire was installed on a Japanese-made FR vehicle with a displacement of 2000cc. After the vehicle drove 50km on a dry asphalt road at an average speed of 120km / h, the difference in wear on both sides of the tire circumferential direction of the center pattern block, middle pattern block and shoulder pattern block of the rear wheel was measured. For each pattern block, 8 measurements were performed at approximately equal intervals in the circumferential direction of the tire, and the average value of all measured values ​​was calculated. Then, the measurement results were expressed as an index using the following formula. The results show that the larger the index, the better the uneven wear resistance. For uneven wear resistance, the performance target value should be above 108.

[0229] (Uneven wear resistance index) = (wear difference of reference comparative example) / (wear difference of each test tire) × 100

[0230] In addition, for the comprehensive performance of fuel efficiency (tires), wet grip performance (actual vehicle), handling stability and uneven wear resistance (the average value of fuel efficiency (tires), wet grip performance (actual vehicle), handling stability and uneven wear resistance), the performance target value should be above 105, preferably above 108, and more preferably above 110.

[0231]

[0232]

[0233]

[0234]

[0235]

[0236]

[0237] From the results of Tables 1 to 3, it can be found that the pneumatic tire of the present invention (the total width of the tire and the buffer layer width of the tire meet the predetermined requirements and the elongation at break and / or compounding of the tread rubber composition meet specific conditions) is excellent in uneven wear resistance when running at high speed. In addition, it can be found that in a preferred embodiment, fuel efficiency, wet grip performance and handling stability when running at high speed are improved and have a good balance.

Claims

1. Passenger car tires, the aspect ratio is 35% to 70%, in, Y is defined by the following formula: Y=(B-16) / A Wherein, when the tire tread is pressed on a flat surface under the condition of applying a normal load, the tire is mounted on a normal rim and is in a normal state with normal internal pressure and no load, A is the total width of the tire, B is the width of the tire's buffer layer, The range of Y values ​​varies according to the flattening ratio as follows: When the flatness is 35% or more and less than 40%, Y is 0.80 or less. When the flatness is 40% or more and less than 45%, Y is 0.79 or less. When the flatness is 45% or more and less than 50%, Y is 0.78 or less. When the flatness is 50% or more and less than 55%, Y is 0.77 or less. When the flatness is 55% or more and less than 60%, Y is 0.75 or less. When the flatness is 60% or more and less than 65%, Y is 0.72 or less. When the flatness is 65% or more and less than 70%, Y is 0.69 or less. When the flatness is 70%, Y is less than 0.

67. The total width A of the tire and the buffer layer width B of the tire are values ​​in mm. The tread rubber composition comprises a rubber component, and the elongation at break of the tread rubber composition measured under the following test conditions is greater than 225%: (Test conditions) Tensile rate: 14.0m / s Temperature: 100℃ Test piece: No. 7 dumbbell-shaped test piece based on JIS K 6251:2017 "Rubber, vulcanized or thermoplastic - Determination of tensile stress-strain properties".

2. The tire for a passenger vehicle according to claim 1, wherein: The tread rubber composition contains silica. In the tread rubber composition, when the content of silica is C and the average primary particle size of silica is D relative to 100 parts by mass of the rubber component, C / D is 3.8 or more, the content C of silica is a value in parts by mass, and the average primary particle size D of silica is a value in nm.

3. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition comprises a nitrogen adsorption specific surface area N2SA of 180 m 2 / g or more of silica.

4. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition includes a silane coupling agent having a mercapto group.

5. The tire for a passenger vehicle according to claim 1 or 2, wherein: The rubber component includes styrene-butadiene rubber.

6. The tire for a passenger vehicle according to claim 1 or 2, wherein: The content of the styrene-butadiene rubber in the rubber component is 60% by mass or more and 95% by mass or less.

7. The tire for a passenger vehicle according to claim 1 or 2, wherein: The rubber component includes butadiene rubber.

8. The tire for a passenger vehicle according to claim 1 or 2, wherein: The total content of styrene in the styrene-butadiene rubber and the butadiene rubber in the rubber component is 25% by mass or more.

9. The tire for a passenger vehicle according to claim 2, wherein: The C is 50 or more and 150 or less.

10. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition includes carbon black.

11. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition includes modified styrene-butadiene rubber.

12. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition includes zinc dithiophosphate.

13. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition includes a thiuram-based vulcanization accelerator.

14. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition includes a tackifying resin.

15. The tire for a passenger vehicle according to claim 1 or 2, wherein: The tread rubber composition includes a processing aid.

Citation Information

Patent Citations

  • Rubber composition and pneumatic tire using it

    JP2009120819A

  • Pneumatic tire

    CN102049968A

  • Pneumatic tire

    CN102438844A